Modification of the Employment Relationship inто the State of Emergency or Emergency Epidemic Situation - Hristova, Janeta (Research Papers, 2021)
The present study analyzes the changes in labor legislation made in order to reduce the negative effects of the crisis caused by SCovid-19 on employment. They extend the powers of employers to change certain elements of the content of employment relationships unilaterally that affect the rights of employees substantially. Adopted suddenly and under the pressure of events, the new regulation needs to be refined to meet correspond the function of labor law to protect employees. The main purpose of the article is based on the normative, formal-logical and deductive method to analyze the legal norms establishing the possibilities for reaction of the employer and to derive the guidelines for increasing the protection of labor in cases of state of emergency or emergency epidemic situation.
Keywords: Change; Employment relationship; Emergency epidemic situation; COVID-19; State of emergency